Evaluation of clinical safety and anthelmintic efficacy of aurixazole administed orally at 24 mg/kg in cattle - Sakamoto, Claudio Alessandro M. [UNESP]; Zanetti Lopes, Welber Daniel [UNESP]; Buzzulini, Carolina [UNESP]; Cruz, Breno Cayeiro [UNESP]; Felippelli, Gustavo [UNESP]; Teixeira, Wes Len F. [UNESP]; Silva, Helenara Machado [UNESP]; Santana, Luis Fernando [UNESP]; Soares, Vando Edesio [UNESP]; Henrique, Carlos Henrique; Oliveira, Gilson Pereira de [UNESP]; Costa, Alvimar Jose da [UNESP] (Elsevier B.V., 2014)
The current study evaluated, in vivo, the clinical safety and the anthelmintic efficacy of 24% aurixazole (24 mg/kg), administered orally, in bovines. Two experiments were conducted: the first one evaluating the clinical safety of 24% aurixazole (24 mg/kg) in cattle, and a second one evaluating the anthelmintic efficacy of aurixazole (24 mg/kg) against gastrointestinal nematodes on naturally infected cattle. Based on the results of clinical safety, no alterations on clinical and haematological signs and on the biochemical values obtained in animals treated orally with aurixazole 24 mg/kg were observed. Regarding the results of reduction or efficacy, obtained by eggs per gram of faeces (EPG) counts, the formulation of aurixazole reached values superior to 99% (arithmetic means) in all post-treatment dates. In two occasions, this formulation reached maximum efficacy (100%). Comparing these results with the reduction percentages obtained by EPG counts, it is possible to verify that the values obtained by all three formulations were compatible with the efficacy results. Aurixazole reached maximum efficacy (100%) against Haemonchus placei, Cooperia spatulata and Oesophagostomum radiatum. Against Cooperia punctata, this formulation reached an efficacy index of 99.99%. Regarding aurixazole, no specific trials were conducted on the field in order to evaluate the behaviour of this molecule against helminths that are resistant to other molecules, specially isolated levamisole and disophenolat: Due to this fact, future studies will be necessary to assess the effectiveness of aurixazole against strains of nematodes that are resistant to levamisole and disophenolat, but the results of clinical safety and efficacy described in this study allow us to conclude that the aurixazole molecule, concomitantly with other measures and orally administered formulations, can be another important tool in the control of nematodes parasitizing bovines. (C) 2014 Published by Elsevier Ltd.
Keywords: Aurixazole; Cattle; Clinical safety; Helminths; Resistance